The European eel as bioindicator of pollution by organochlorines in Campania region river (Italy) - DELLA ROCCA, Giorgia; DI SALVO, Alessandra; M. T. CLAUSI; E. ESPOSITO; A. LUCISANO; M. C. FERRANTE (Journal of Veterinary Pharmacology and Therapeutics, 2009)
Introduction Organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) are ubiquitous environmental contaminants, which tend to bioaccumulate in lipid tissues of living organisms and eventually become dangerous for wildlife and humans [1]. Ingestion is the main source of human exposure to persistent organic pollutants, and, in particular, the consumption of seafood from contaminated areas [2]. There are few papers regarding the state of contamination of the Campania region by organochlorine pollutants; such studies report the presence of high contamination levels in various fish species and fish-eating bird species [3,4,5]. In the present study, the levels of some persistent organic pollutants in European eels from the Garigliano river have been investigated. Both behavioural and alimentary habits, and the high lipid content have prompted some to propose that eels act as an excellent bioindicator of environmental pollution by persistent contaminants. Material and Methods European eels (Anguilla anguilla) were caught in proximity of the estuary of the Garigliano river from October 2005 to July 2006. Homogenized tissue samples (muscle + skin) were extracted by petroleum/acetone, cleaned up by n-hexane/acetonitrile repartition and separated into three fractions by passing through a glass column packed with Florisil. Extracts were analysed using a gas chromatograph equipped with an electron capture detector. Concentrations of hexachlorobenzene (HCB), DDTs, dieldrin and 20 PCBs congeners were determined for each sample. Organochlorine concentrations were expressed as nanograms per gram on a lipid weight basis. The statistical analysis was performed by standard descriptive statistics and by the mean test relative to the residual concentrations of the analysed compounds. Results PCBs were the most abundant pollutants followed by DDTs, dieldrin and HCB. PCBs were found in all the samples at concentrations ranging from 119.69 to 2156.95 ng•g-1 f.w., and the sum of the seven “target” congeners (IUPAC nos. 28, ...